Modified extradural temporopolar approach with mini-peeling of dura propria for paraclinoid and/or parasellar tumors: Operative technique and nuances - Otani, Naoki (Surg Neurol Int, 2017)
BACKGROUND: Modified extradural temporopolar approach (EDTPA) with mini-peeling of the dura propria can provide extensive exposure of the anterior clinoid process and early exposure, as well as complete mobilization and decompression of the optic nerve and internal carotid artery, which can prevent intraoperative neurovascular injury for paraclinoid and/or parasellar lesions. The present study investigated the usefulness of this modified technique and discusses the operative nuances. METHODS: We retrospectively reviewed medical charts of 27 consecutive patients with neoplastic paraclinoid and/or parasellar lesions who underwent this modified approach between September 2009 and August 2016. RESULTS: Preoperative visual acuity worsened in 2 patients (7.4%), and worsening of visual field function occurred in 2 patients (7.4%). Postoperative outcome was good recovery in 25 patients (92.6%) and moderate disability in 2 (7.4%). No operation-related mortality occurred in the series. CONCLUSIONS: The modified EDTPA is safe and recommended for surgical treatment of paraclinoid and/or parasellar tumors to reduce the risk of intraoperative optic neurovascular injury.